Secondary analysis and literature review of community rehabilitation and intermediate care: an information resource - Steven M Ariss; Pamela M Enderby; Tony Smith; Susan A Nancarrow; Mike J Bradburn; Deborah Harrop; Stuart G Parker; Ann McDonnell; Simon Dixon; Tony Ryan; Alexandra Hayman; Michael Campbell (National Institute for Health Research, 2015)
Background and design: This research was based on a reanalysis of a merged data set from two intermediate care (IC) projects in order to identify patient characteristics associated with outcomes [Nancarrow SA, Enderby PM, Moran AM, Dixon S, Parker SG, Bradburn MJ, et al. The Relationship Between Workforce Flexibility and the Costs and Outcomes of Older Peoples' Services (COOP). Southampton: National Institute for Health Research (NIHR) Service Delivery and Organisation (SDO); 2010 and Nancarrow SA, Enderby PM, Ariss SM, Smith T, Booth A, Campbell MJ, et al. The Impact of Enhancing the Effectiveness of Interdisciplinary Working (EEICC). Southampton: NIHR SDO; 2012]. Additionally, the impact of different team and staffing structures on patient outcomes and service costs was examined, when possible given the data sets, to enable identification of the most cost-effective service configurations and change over time with service provision. This secondary analysis was placed within updated literature reviews focused on the separate questions. Research objectives: (1) To identify those patients most likely to benefit from IC and those who would be best placed to receive care elsewhere; (2) to examine the effectiveness of different models of IC; (3) to explore the differences between IC service configurations and how they have changed over time; and (4) to use the findings above to develop accessible evidence to guide service commissioning and monitoring. Setting: Community-based services for older people are described in many different ways, among which are IC services and community rehabilitation. For the purposes of this report we call the services IC services and include all community-based provision for supporting older people who would otherwise be admitted to hospital or who would require increased length of stay in hospital (e.g. hospital at home schemes, post-acute care, step-up and step-down services). Participants: The combined data set contained data on 8070 patient admissions from 32 IC teams across England and included details of the service context, costs, staffing/skill mix (800 staff), patient health status and outcomes. Interventions: The interventions associated with the study cover the range of services and therapies available in IC settings. These are provided by a wide range of professionals and care staff, including nursing, allied health and social care. Outcome measures: (1) Service data - each team provided information relating to the size, nature, staffing and resourcing of the services. Data were collected on a service pro forma. (2) Team data - all staff members of the teams participating in both studies provided individual information using the Workforce Dynamics Questionnaire. (3) Patient data - patient data were collected on admission and discharge using a client record pack. The client record pack recorded a range of data utilising a number of validated tools, such as demographic data, level of care (LoC) data, therapy outcome measure (TOM) scale, European Quality of Life-5 Dimensions (EQ-5D) questionnaire and patient satisfaction survey. Results: (1) The provision of IC across England is highly variable with different referral routes, team structures, skill mix and cost-effectiveness; (2) in more recent years, patients referred to IC have more complex needs associated with more severe impairments; (3) patients most likely to improve were those requiring rehabilitation as determined by levels 3, 4 and 5 on the LoC (> 40% for impairment, activity and participation, and > 30% for well-being as determined on the TOM scale); (4) half of all patients with outcome data improved on at least one of the domains of the TOM scale; (5) for every 10-year increase in age there was a 6% decrease in the odds of returning home. The chance of remaining or returning home was greater for females than males; (6) a high percentage of patients referred to IC do not require the service; and (7) teams including clinical support staff and domiciliary staff were associated with a small relative improvement in TOM impairment scores when compared with other teams. Conclusions: This study provides additional evidence that interdisciplinary teamworking in IC may be associated with better outcomes for patients, but care should be taken with overinterpretation. The measures that were used within the studies were found to be reliable, valid and practical and could be used for benchmarking. This study highlights the need for funding high-quality studies that attempt to examine what specific team-level factors are associated with better outcomes for patients. It is therefore important that studies in the future attempt empirically to examine what process-level team variables are associated with these outcomes. Funding: The NIHR Health Services and Delivery Research programme.